The Effect of Skill Competition on Employee Learning Motivation in Manufacturing Companies with Coach Quality as a Moderator Variable - Andaryanto, Andaryanto; Arief Noviarkahman Zagladi (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to analyze the effect of skills competitions on employee learning motivation in manufacturing companies, as well as explore the role of coach quality as a moderator variable in the relationship. The research design used is explanatory research, with the sample consisting of employees who have participated in a skills competition at PT Tjiwi Kimia Paper Mill, Tbk. Data collection techniques were conducted through questionnaires and data were analyzed using linear regression statistical methods. The results show that skill competitions have a positive significant influence on employee learning motivation, accounting for 68,3% of the variation (R2 = 0.683, p < 0.001). Furthermore, the quality of trainers moderated this relationship, with higher quality trainers enhancing the positive effect of skill competitions on learning motivation (interaction coefficient = 0.271, p = 0.034). These findings underscore the importance of well-designed competitions and competent trainers in fostering employee development, offering practical insights for creating impactful training program